REVITALISASI PEMBELAJARAN BAHASA INDONESIA MELALUI KOMIK DIGITAL UNTUK PENINGKATAN KEMAMPUAN MEMBACA DI SEKOLAH DASAR - Ayudianingsih, Nirma Meirista; Sutomo, Moh; Amini, Mukti (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2026)
The low reading ability of second-grade students at Babadan Elementary School, with an average achievement of only 55%, emphasizes the need for more engaging and child-friendly learning media. Canva-based digital comics were chosen because they present engaging visuals, simple storylines, and enjoyable learning experiences. This study aims to develop digital comic media and test its validity, practicality, and effectiveness in improving elementary school students' reading abilities. The study used the ADDIE Research and Development (R&D) model, including needs analysis, media design, product development, implementation through pretest-posttest, and evaluation using the N-Gain Score. The research subjects were second-grade students at Babadan Elementary School and Bodor Elementary School 1. The results showed that the media's validity was very high (media experts 97.22%, language experts 93.75%, material experts 96.66%), confirming that the media met the standards for design, language, and material feasibility. In terms of practicality, the media scored 96.87%, was easy to use, understand, and was engaging for students. Meanwhile, effectiveness is evident from the improvement in student learning outcomes with a moderate N-Gain category, indicating the media is able to consistently improve comprehension. This research contributes theoretically and practically by providing a feasible, practical, and effective digital comic medium, while also enriching the literature on innovative media development for reading instruction for lower-grade students.